The Variability of Seed Viability and Seed Vigour of Mindi (Melia azedarachlinn.) from Several Populations in The Community Forest of West Java - Yulianti, Yulianti Bramasto; Nurheni , Nurheni Wijayanto; Iskandar, Iskandar Z Siregar; Darma, I.G.K. Tapa Darma (Jurnal Wasian, 2016)
The procurement of good quality seeds for the development of mindi (Melia azedarach L.) in the community forest is absolutely necessary. The purpose of this research is to investigate the diversity of the viability and seedling vigor of mindi from different populations with various treatments of dormancy breaking. The sample materials were mindi seeds that were collected from 6 locations (6 seed lots) or seed sources which were located in the community forest of West Java. There are 10 treatments of dormancy breaking that were applied in this study. The experiment design was Randomized Complete Design (RAL). The breaking dormancy was focused to the delignification of hard seed coat. Results showed that the most effective dormancy breaking for mindi seed was soaking in consentrated Sulfuric Acid (H2SO4) as long as 30 to 45 minutes. The first count for germination of mindi was on the 16 day and the final count was on the 31 day.The average value of germination percentage (DB) for all seed sources was 40 %, while the highest which is 60% was mindi from Sumedang seed source. The highest value of germination rate that is 6,543%/etmal was seed from Sumedangand seed from Gambung was the lowest (1,400 %/etmal).